2021
DOI: 10.1111/desc.13090
|View full text |Cite
|
Sign up to set email alerts
|

Vocal development in a large‐scale crosslinguistic corpus

Abstract: This study evaluates whether early vocalizations develop in similar ways in children across diverse cultural contexts. We analyze data from daylong audio-recordings of 49 children (1-36 months) from five different language/cultural backgrounds. Citizen scientists annotated these recordings to determine if child vocalizations contained canonical transitions or not (e.g., "ba" versus "ee").Results revealed that the proportion of clips reported to contain canonical transitions increased with age. Further, this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 100 publications
3
28
0
1
Order By: Relevance
“…The reason that mothers exhibit different behaviour with male and female infants could be due to the vocalizations these infants produce, but findings to date are mixed on whether sex might influence infant vocalization, particularly in whether it occurs in a manner that is perceptible to caregivers. One recent study, Oller et al (2020), found that male infants babble more than females, however Cychosz et al (2021) did not find evidence in favour of an effect of child sex on canonical babbling ratio in their examination of the corpus we will use. While to our knowledge there have been no studies of the accuracy of caregiver perception of sex via infant vocalization, there is at least some reason to believe that sex-related differences could exist, as estrogen has been positively correlated with verbal development while testosterone has been negatively correlated (e.g.…”
Section: Adult Perception Of Infant Sex In Vocalizationmentioning
confidence: 75%
“…The reason that mothers exhibit different behaviour with male and female infants could be due to the vocalizations these infants produce, but findings to date are mixed on whether sex might influence infant vocalization, particularly in whether it occurs in a manner that is perceptible to caregivers. One recent study, Oller et al (2020), found that male infants babble more than females, however Cychosz et al (2021) did not find evidence in favour of an effect of child sex on canonical babbling ratio in their examination of the corpus we will use. While to our knowledge there have been no studies of the accuracy of caregiver perception of sex via infant vocalization, there is at least some reason to believe that sex-related differences could exist, as estrogen has been positively correlated with verbal development while testosterone has been negatively correlated (e.g.…”
Section: Adult Perception Of Infant Sex In Vocalizationmentioning
confidence: 75%
“…Such diversity is also deeply necessary in order to minimize biases in operationalizing everyday behaviors as they arise in many contexts (e.g., Cychosz et al, 2020a). Aggregating contributions from many individuals and teams means that smaller efforts cumulate to larger insights, making team science well-matched to the challenge of annotating many hours of infants' everyday lives (see also Cychosz et al, 2021). Frameworks designed to address issues that arise in research that is distributed over time and teams include co-authorship and contributorship models (Holcombe, 2019;Moshontz et al, 2021), pre-registration of secondary data analyses (Van den Akker et al, 2019), and protocols devised for widespread use coupled with practical tutorials to support incremental contributions (Soderstrom et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, theorists can plan to analyze only those portions of their data that are reliably annotated. Multiple annotators can judge individual episodes of everyday behavior, and then only those episodes that are annotated identically by multiple annotators are analyzed (e.g., Fausey et al, 2016 ; Cychosz et al, 2021 ). With this approach, one need not drop an entire project because some of the data are difficult to annotate and contribute to a low “overall” reliability.…”
Section: Principle 4: Transparent Rationale For Assessing Reliability Of Annotations In Many Hours Of Everyday Lifementioning
confidence: 99%
“…Such diversity is also deeply necessary in order to minimize biases in operationalizing everyday behaviors as they arise in many contexts (e.g., Cychosz et al, 2020a). Aggregating contributions from many individuals and teams means that smaller efforts cumulate to larger insights, making team science well matched to the challenge of annotating many hours of infants' everyday lives (see also Cychosz et al, 2021). Rigorously quantifying everyday experiences of infants across the world is necessary in order to achieve theories of experience-dependent change that respect the diversity of infants' experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic review also reveals various solutions to accounting for this challenge. For example, some routes to discovery are amenable to multiple annotators judging individual episodes of everyday behavior and only those episodes with a plurality of identical annotations are retained for analyses (e.g., Cychosz et al, 2021;Fausey et al, 2016). That is, one need not throw out the proverbial baby with the bathwater if some but not all portions of everyday data are challenging to annotate.…”
Section: Principle 4: Transparent Rationale For Assessing Reliability Of Annotations In Many Hours Of Everyday Lifementioning
confidence: 99%